Creative Percussion “Ilang” | Tabuh Kreasi “Ilang” - I Putu Pryagus Nyoman Sana; Ni Putu Hartini (GHURNITA: Jurnal Seni Karawitan, 2023)
Ilang is a creative percussion composition inspired by the life of a stylist who feels the loss of a mother he loves.  In the Balinese Indonesian dictionary, it is explained how the word Ilang means lost or lost.  The meaning of loss can be in the form of sadness and suffering or a slap on the quality of fortitude and self-preparedness.  Loss shows a sense of not being completely whole, feeling lacking without the presence of something or someone.  Seeing the phenomenon that occurred, an inspiration emerged to lift Ilang into a title for musical composition in the form of creative percussion.  The composition of this creative percussion uses the media expressed by Gamelan Semare Pagulingan Saih Pitu and is supported by vocal musicians (Gerong) as a medium for delivering messages that the stylist wants to convey to art connoisseurs.  The method of creation used in Ilang's percussion works is the Panca Sthiti Ngawi Sani method which includes;  1 stage of inspiration (Ngawirasa), 2 stages of exploration (Ngawacak), 3 stages of conception (Ngarencana), 4 stages of execution (Ngawangun) and the last 5 stages of production (Ngebah).  This work is approximately 13 minutes long, this work cultivates melodies, rhythms, and dynamics that are so harmonious and still uses the concept of tradition by using contemporary elements to create new nuances. Keywords: Creative Percussion, Ilang, Panca Sthiti Ngawi Sani